Extended osteoplastic maxillotomy for total excision of giant multicompartmental juvenile nasopharyngeal angiofibroma - Koshy Santosh; George Mercy; Gupta Ashish; Daniel Roy (Wolters Kluwer Medknow Publications, 2008)
Juvenile nasopharyngeal angiofibroma (JNA) is a rare vascular neoplasm occurring almost exclusively in adolescent males. Although benign, it is often locally aggressive and can erode into surrounding tissues and structures resulting in significant morbidity and mortality. In 20% of cases, there is intracranial extension. In this paper, we report on the total excision of a large, recurrent JNA with intracranial extension into the middle cranial fossa encroaching into the cavernous sinus, by right temporal craniotomy and extended osteoplastic maxillotomy.